Extraarticular Supramalleolar Osteotomy in Asymmetric Varus Ankle Osteoarthritis. (August 2019) - Krähenbühl, Nicola; Akkaya, Mahmut; Deforth, Manja; Zwicky, Lukas; Barg, Alexej; Hintermann, Beat
Background: In recent years, supramalleolar osteotomy has become a valuable alternative for treatment of ankle osteoarthritis. The aim of this study was to investigate whether the preoperative stage of ankle osteoarthritis or tilt of the talus in the ankle mortise impacts radiologic and clinical outcomes following a supramalleolar osteotomy. Methods: Forty-four patients who underwent a supramalleolar osteotomy for posttraumatic asymmetric varus ankle osteoarthritis were included. Subgroups were formed according to the preoperative stage of ankle osteoarthritis and the tilt of the talus in the ankle mortise. The radiographic and clinical outcomes of each subgroup were compared, and survival rates calculated. Results: Ankles with a preoperative Takakura stage of 2 and 3a showed a significant higher survival rate at 5 years (88% [95% CI, 67-100] and 93% [95% CI, 80-100]) compared with ankles with a preoperative Takakura stage of 3b (47% [95% CI, 26-86]; P = .044). The 5-year survival rate for patients with a preoperative tilt of the talus in the ankle mortise of 4-10 degrees was 85% (95% CI, 68-100), while patients with a preoperative tilt of >10 degrees showed a 5-year survival rate of 65% (95% CI, 46-93; P = .117). Conclusion: Supramalleolar osteotomy was a valuable treatment option for early to mid-stage posttraumatic asymmetric varus ankle osteoarthritis. Level of Evidence: Level IV, retrospective cohort study.